A trajetória de uma educadora axiniense: entre desafios e superações - Lemos, Eunice Moreira de (Brasil, 2024)
This work reports all the experiences I had during the Pedagogy course and the knowledge acquired throughout this journey. To carry out this work, I chose two schools: the first was the Francisco Bezerra Batista Municipal School, and the second was the João Ferreira da Fonseca State School, as sources of research and observations. The internships were important to review and improve my practice, to become a more dedicated professional, still paying attention to everyone involved in the educational process. It is worth mentioning that my memorial tells the difficulties and contributions of the course to my teaching practice and how valuable it was to my professional life. It is important to remember that before the course I did not have a clearer view of this degree. Today I realize that I am a different professional and with more possibilities to apply innovative practices to try to achieve quality education for children. Therefore, the objective of this work is to present everything that the Pedagogy course provided me, always highlighting the learning I acquired during internships to emphasize the improvement of my pedagogical practice and thus contribute to education in the municipality of Borba.